2021
DOI: 10.1007/s10342-021-01369-w
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fencing on seedling establishment during reforestation of oak stands: a comparison of artificial and natural regeneration techniques including costs

Abstract: In temperate Europe, oak-dominated forests are widespread, supporting high biodiversity and providing important ecosystem services. Insufficient natural regeneration has, however, been a concern for over a century. The objective of this study was to gain insights into differences in regeneration success using artificial and natural regeneration techniques for reforestation of oak (Quercus robur L.) stands. We monitored seedlings following planting, direct seeding and natural regeneration over five years in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
(61 reference statements)
2
12
0
Order By: Relevance
“…Equally apparent was the potential of natural oak regeneration, which was the basis of the observed oak regeneration in the majority of stands. Together with the findings by Löf et al [41], who evaluated the costs for oak natural regeneration and found them to be the lowest, this results in an additional potential for operational savings or at least compensation.…”
Section: Long-term Development and Survival Of The Regenerationsupporting
confidence: 60%
See 1 more Smart Citation
“…Equally apparent was the potential of natural oak regeneration, which was the basis of the observed oak regeneration in the majority of stands. Together with the findings by Löf et al [41], who evaluated the costs for oak natural regeneration and found them to be the lowest, this results in an additional potential for operational savings or at least compensation.…”
Section: Long-term Development and Survival Of The Regenerationsupporting
confidence: 60%
“…However, Ligot et al [34] demonstrated that beech outperformed oak throughout the light gradient and concluded that silvicultural control of the canopy cover is not sufficient in mixed oak and beech regenerations. Consequently, to keep survival rates high the management of mixed oak regenerations has to consider competing woody species [37,38] and ground vegetation [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Habrova and Pavlis (2017) observed an increasing rate of seedling survival and development for Dracaena cinnabari with increasing time of their exclosure on the Firmihin Plateau, Socotra Island, Yemen. Similarly, Löf et al (2021) reported a significant height increment in both planted and naturally regenerated Quercues robur seedlings within fenced areas compared to non-fenced areas.…”
Section: Discussionmentioning
confidence: 84%
“…The third criterion evaluates the height of the regeneration individuals in two classes: (1) individuals with a height between 0.5 and 1.3 m and (2) individuals with a height higher than 1.3 m. It can be considered a surrogate of the sapling's development. The height of the saplings is the parameter more described in the previous literature (Long and Jones, 1996;Harmer, 2005;Dobrowolska, 2006;Esquivel et al, 2007;Löf et al, 2021). The fourth criterion evaluates the diameter of regeneration individuals measured at 1.30 m, that is when the regeneration tree can be considered installed (when it overcomes the period of high mortality rate) (Assmann, 1970).…”
Section: Natural Regeneration Tree Classificationmentioning
confidence: 99%
“…characteristics. Most regeneration studies evaluate regeneration by quantifying its density and height (Harmer, 2005;Acácio et al, 2007;Barrere et al, 2021;Bolibok et al, 2021;Löf et al, 2021). The traits of the individuals are not evaluated.…”
mentioning
confidence: 99%